Endoscopic endonasal intradural pituitary transposition for resecting retroinfundibular lesions: technique notes and a single institute experience - Ke, Daibo; Yang, Shaocheng; Lin, Yifeng; Liu, Hao; Chen, Wei; Lv, Tao; Yue, Xiang; Xu, Ling; Xiao, Shunwu (Frontiers in Endocrinology, 2025)
BackgroundThe endoscopic endonasal approach (EEA) is the mainstay of resection for lesions in the retroinfundibular area and the prepontine and interpeduncular cisterns. Owing to the anatomical barrier of structures such as the pituitary gland (PG)/pituitary stalk (PS), dorsum sellae (DS) and posterior clinoid process (PCPs), sufficient tumour resection often requires displacement of the pituitary gland and varying degrees of bony resection.MethodsWe retrospectively studied the clinical data of 23 patients, from June 2016 to February 2023,who underwent endoscopic endonasal intradural pituitary gland transposition (PGT) as well as dorsectomy and posterior clinoidectomy for the treatment of lesions involving the retroinfundibular area, prepontine cistern and interpeduncular cisterns. Outcomes, including postoperative complications and the extent of tumour resection (EOR), were evaluated.ResultsAmong the 23 patients with tumours, 16 had craniopharyngiomas, 3 had germ cell tumours, 2 had epidermoid cysts, and 2 had gliomas. Fifteen patients underwent unilateral PGT and ipsilateral dorsectomy, and 8 patients underwent ipsilateral posterior clinoidectomy. Ten patients with visual impairment improved, and none of the patients experienced cranial nerve palsy postoperatively. Fourteen patients developed hypopituitarism, and 8 patients experienced diabetes insipidus (DI) postoperatively, 6 and 4 of theses patients recovered after 2–4 weeks of replacement therapy. Twelve patients with intraoperative high-flow CSF leakage underwent an average of 7 days of early postoperative lumbar drain (LD). Among them, 4 patients developed an infection, which was cured by 10 days of antibiotic treatment combined with LD. None of the patients experienced constant CSF leakage at the discharge. Gross total resection (GTR) was achieved in 19 tumour patients, and near-total resection (NTR) was achieved in 4 patients. The average follow-up period was 26 months, and magnetic resonance imaging (MRI) revealed no tumour recurrence in 22 patients.ConclusionTumours of the retroinfundibular area, prepontine and interpeduncular cisterns can be safely removed via the PGT technique. The intradural PGT technique combined with flexible dorsectomy and posterior clinoidectomy has obvious advantages, including less intraoperative bleeding, more effective pituitary transposition, and good preservation of pituitary function. Owing to the complexity of these regions, this technique should be performed by experienced endoneurosurgeons.